IDENTIFIKASI MIKROBIA PADA FERMENTASI BIJI KOPI ARABIKA (Coffea arabica Linn) - Erryana Martati (JURNAL AGROTEKNOLOGI, 2007)
Mucilage in coffee bean should be removed because it inhibits coffee bean drying. One way of removing mucilage is by fermentation. Microbes presented naturally during coffee fermentation can utilize organic substances in coffee bean and produces mucilage. During fermentation, pectin, the main component in mucilage, can be hydrolyzed by pectinolytic microorganism. The aim of this research is to identify the microbes involved during coffee fermentation. The fermentation was done in laboratory with 2 replications, and samples were analyzed for identifying the type of microorganisms. The analysis showed that the microbes found during Arabica coffee fermentation were bacteria, lactic acid bacteria, yeast, and fungus. Kinds of bacteria group were Bacillus, Acinetobacter, Enterobacteriae and Moraxella. Type of the Lactic acid bacteria were Lactobacillus and Leuconostoc mesenteroides. Group of yeast were Zygoascus Hellenicus, Candida halonitratophila, and Torulaspora delbrueckii. Fungi group were Penicillium citrinum, Penicillium janthinellum, Aspegillus niger, Verticillium glaucum, Verticillium terrestre and Acremonium vitis. Bacillus sp and Enterobacteriaceae have an important role in pectin degradation. Possibly the fungus do not have roles in coffee fermentation since they grow at surface part during fermentation. Keywords: coffee fermentation, microorganism, Arabica coffee